Main Modernization Elements of the Educational System with the Return of Democracy in Chile (Training and Practice : Journal of Educational Sciences, 2009)
During the last century Chile was part of the news for three main reasons. Until 1973 it was well-known because of his democracy; between 1973 and 1990, because of the military dictatorship commanded by the General Augusto Pinochet, and finally from 1990 to these days because of the return of democracy. In educational matters, due to the “Liceo ” (High school), the origin of a solid and meaningful middle class, was caused and made possible that two political parties consisting ofpeople from that social class could give “government ” to the countries in these important periods: The radical party influenced by their laicize background and the Christian democratic party influenced by their Christian and humanist inspiration.The objective of this article is to describe the modifications in the educational system during these last twenty years in Chile and analyze if these changes help to find the way to become a developed country.